PENINGKATAN KESEHATAAN DAN EKONOMI MASYARAKAT MELALUI PEMBUATAN TANAMAN OBAT KELUARGA (TOGA) DI DESA CIPTA KARYA - Linda, Riza; Rafdinal, Rafdinal (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2022)
Family Medicinal Plants or can be abbreviated as TOGA is a type of plant that is cultivated in the yard of the house. Cultivated plants not only provide family health but also provide the beauty of the yard. The development of TOGA in Cipta Karya Village which is a tourist village has been socialized but the management and utilization of TOGA has not run optimally. The introduction of medicinal plant species and their use is still largely unknown to the public. The purpose of this community service activity program is to increase the income of family members through a program to utilize family medicinal plants as family herbs. The activities carried out were socialization and demonstrations about the potential and utilization of medicinal plants in the community in Cipta Karya village. Socialization about TOGA in addition to supporting health, also provides environmental beauty, plant conservation and can provide family welfare. The results of this activity indicate an increase in participants' knowledge of plant species that have potential and have medicinal properties and how to make TOGA so that there is an aesthetic and beautiful environment and can improve the family's economyKey word: Family Medicinal Plants (TOGA); Health; Family Economy